Opportunities and Challenges in Energy‐Related Boomtowns: Implications for Family and Consumer Science Professionals. (June 2016) - Fitzgerald, Margaret A.; Muske, Glenn; Haynes, George; Lee, Yoon G.
Abstract : Economic prosperity in energy‐dependent regions has created unique opportunities and challenges for individuals, families, and communities. This study demonstrates how theory and research can guide family and consumer science (FCS) professionals in helping people adapt to disruptions caused by economic cycles. Evidence is derived from primary interviews with family business owners and others in the Bakken area of western North Dakota, and secondary data from the Uinta Basin area of Utah. The study provides guidance to FCS professionals interested in helping people understand challenges, adjust to change, and implement best practices in communities impacted by boom and bust cycle disruptions.